A comparative study of heritage visitors' perceptions of time in the modern era. Issue 5 (4th March 2023) - Korani, Zohreh; Sam, Fatemeh
ABSTRACT : This study aims to identify the factors affecting the formation of visitors' perception of time in the two heritage sites of Naqsh-e Jahan and Merdeka from the interpretive approach. The explanatory method was used to ensure a deep understanding of visitors' perceptions. Initially, 376 questionnaires were collected in Naqsh-e Jahan and 366 questionnaires in Merdeka. The Friedman test showed the differences between visitors' prioritization of time perception variables. It was concluded that the sub-indices of environmental variables and special days rejected the hypothesis. In the qualitative part, researchers used methods of interviews and narrative stories based on their observations and lived experiences. Narrative descriptions allowed researchers to become aware of visitors' perceptions and to make meaningful interpretations in which social context and culture are considered. Qualitative data analysis was performed by the triple coding method. 4 core categories were obtained, based on which the perception of time was formed in the visitors' minds. These categories are sense of rhythm, speed of time, sense of change, and normative components of each country. It states that just as the amplification of spatial norms in a particular place is effective in strengthening the sense of place, it can also be generalized in time.